1976
DOI: 10.1159/000301329
|View full text |Cite
|
Sign up to set email alerts
|

Cell Contacts and Distribution of Nerves in the Smooth Muscle of Estrogen-Dominated Rabbit Oviduct

Abstract: The types of cell-to-cell contacts and the relationship between the nerve endings and the smooth muscle of the estrogen-treated rabbit oviduct have been investigated. The cell contacts most consistently found in the oviduct were simple appositions, with a 20-nm cell separation, which occasionally included a more dense region, and interdigitations of muscle cell processes with the same separation distances. Very rarely, wider intermediate contacts were present. Gap junctions (nexuses) were absent. It seems like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In a detailed study of the types of cell-to-cell contacts in the smooth muscle layers of the rabbit oviduct, Henderson et al (8) concluded that cell-to-cell contacts were almost exclusively of the type known as simple appositions (7), and the same conclusion has recently been reached by Seki et al (15). Simple appositions were the only type of contact seen by us in the monkey oviduct.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In a detailed study of the types of cell-to-cell contacts in the smooth muscle layers of the rabbit oviduct, Henderson et al (8) concluded that cell-to-cell contacts were almost exclusively of the type known as simple appositions (7), and the same conclusion has recently been reached by Seki et al (15). Simple appositions were the only type of contact seen by us in the monkey oviduct.…”
Section: Discussionsupporting
confidence: 56%
“…We also decided to compare the numbers of nerves in the isthmus of the monkey with the numbers in the isthmus of the rabbit, using blocks of rabbit tissue from an earlier study by this laboratory (8). In the monkey the number of nerve profiles per muscle cell nucleus was 0.03, but it was 0.26 in the rabbit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…plexuses are present alongside with ICC, further experiments are needed to tell whether the effect is due to a mechanoreceptor function of ICC or other structures. Before leaving this theme, an exciting perspective is revealed by the fact that peg-and-socket junctions have been observed and described in a variety of smooth muscle organs, including other regions of the digestive tract (e.g., colon and pylorus, Nagasawa and Suzuki, 1967), vas deferens (e.g., Lane and Rhodin, 1964), the ureter (Nagasawa and Suzuki, 1967), the oviduct (e.g., Henderson et al, 1976), airway smooth muscle (Daniel et al, 1986), and, in particular, vascular smooth muscle (e.g., Taugner et al, 1984). Whether the same type of junction may couple smooth muscle cells and pacemakers outside the digestive tract remains to be seen, but a general role in autoregulation of smooth muscle tonus is a distinct possibility.…”
Section: The Developing Knowledge Of the Implication Of Iccmentioning
confidence: 99%
“…Close contacts and intermediate junc tions were found in the reproductive tract of other smooth muscle systems that exhibit synchronized contraction [Garfield and Daniel, 1974;Henderson et al, 1976], These junctions might coordinate smooth muscle activity at the time of ovulation by forming a low resistance pathway for con duction of electrical activity, or by allowing some other type of chemical cell-to-cell interaction [Henderson et al, 1976]. The frequency of contractions of the ovarian ligament varies during the menstrual cycle [Decker, 1951;Mohsin and Pennefother, 1979].…”
Section: Discussionmentioning
confidence: 99%